Isolation, Structure Elucidation and Biological Activity of Natural Products - Takahashi, Jacqueline Aparecida (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Issue focuses on processes related to the research of natural products dereived from plants (Bauhinia forficata, Placolobium vietnamense, Tamarix chinensis, Peperomia obtusifolia, Cymbidium ensifolium, Dendrobium delacourii, Turnera subulata, Eruca sativa, Miconia chamissois and Persea americana) and microorganisms (Streptomyces tricolor, Lacticaseibacillus rhamnosus, Gonatophragmium triuniae, Penicillium bissettii and P. glabrum) as well as spectroscopic data from a significant number of natural products, 13C-NMR data from 504 pentacyclic triterpenoids isolated from plants of the Celastraceae family and UV, IR, 1H and 13C-NMR data of the 192 chromones.